Fellowship Training Is a Significant Predictor of Sports Medicine Physician Social Media Presence - Brian LaGrant, B.S; Sergio M. Navarro, M.D., M.B.A; Jacob Becker, M.D; Hashim Shaikh, B.S; Irvin Sulapas, M.D; Theodore B. Shybut, M.D (Elsevier, 2021)
Purpose: To quantify social media use of professional sports team physicians on popular platforms and analyze differences between users and nonusers. Methods: Team physicians for professional sports teams in the National Football League, National Hockey League, Major League Baseball, and National Basketball Association were identified and characterized based on training background, practice setting, and geographic location. Rates of social media presence on Facebook, Twitter, LinkedIn, Instagram, and ResearchGate were determined. Differences between social media users and nonusers were analyzed. Results: In total, 505 professional team physicians were identified across 4 major professional sports; 64.6% of physicians were orthopaedic surgeons. Of 505 physicians, 65.7% had a social media presence. More specifically, 21.8% had a professional Facebook page, 22.6% a professional Twitter page, 52.1% a LinkedIn profile, 21.4% a ResearchGate profile, and 9.1% an Instagram account. Fellowship-trained physicians (P = .008) had greater odds of having a social media presence. Conclusions: Nearly two-thirds of professional team physicians have a social media presence, most commonly LinkedIn. Fellowship training is a significant predictor of sports medicine physician social media presence. Sports league affiliation, training background, practice setting, and geographic location are unrelated to social media presence. Level of Evidence: IV, cross-sectional study.